Vaccine confidence in the time of COVID-19 - Harrison, Emily A.; Wu, Julia W. (European journal of epidemiology, 2020)
In the early months of the COVID-19 epidemic, some have wondered if the force of this global experience will solve the problem of vaccine refusal that has vexed and preoccupied the global public health community for the last several decades. Drawing on historical and epidemiological analyses, we critique contemporary approaches to reducing vaccine hesitancy and articulate our notion of vaccine confidence as an expanded way of conceptualizing the problem and how to respond to it. Intervening on the rush of vaccine optimism we see pervading present discourse around the COVID-19 epidemic, we call for a re-imagination of the culture of public health and the meaning of vaccine safety regulations. Public confidence in vaccination programs depends on the work they do for the community—social, political, and moral as well as biological. The concept of public health and its programs must be broader than the delivery of the vaccine technology itself. The narrative work and policy actions entailed in actualizing such changes will, we expect, be essential in achieving a true vaccine confidence, however the public reacts to the specific vaccine that may be developed for COVID-19.